Development of Interactive Learning Media Based on Lectora Inspire on Excretion System Materials - Rosmayanti Dalimunte; Rohani Rohani (Jurnal Penelitian Pendidikan IPA, 2022)
This development research aims to determine the feasibility of Lectora Inspire-based interactive learning media and its effectiveness on the learning outcomes of class XI students. This research was conducted at MAN Labuhanbatu by focusing on the development of Lectora Inspire-based interactive learning media on excretion system materials in class XI. This research method uses the ADDIE model development research method. This data collection technique uses questionnaires, and observation sheets. The results of the study stated that from three validators the media expert validators gave a score of 80% (Feasible). The material expert also provided an 88% final result with the category "Very Decent". The assessment response in teachers when conducting learning trials received a "very decent" score of 88%. The results of research on the application of Lectora Inspire-based interactive learning media to the subject matter of the excretory sub-system biology to student learning outcomes obtained very effective results. get a gain score of more than 29. It can be concluded that this developed medium is very effectively used in learning for class XI.